194 Natalizumab treatment for MS: UK and global results from TOP. Issue 12 (14th November 2019) - Nicholas, Richard; Harrower, Timothy; Jiang, Xiaoyu; Licata, Stephanie; Vonsy, Jean
Abstract : Introduction: The TYSABRI Observational Program (TOP) is the largest real-world study in natalizumab-treated relapsing-remitting MS patients. Country-specific data, alongside global data, can provide information on natalizumab's effectiveness in local practice. Methods: Annualised relapse rate (ARR) and cumulative probability of 24-week confirmed disability worsening (CDW; Expanded Disability Status Scale [EDSS] score increase from baseline of ≥1.5 from 0.0, ≥1.0 from 1.0–5.5, or ≥0.5 from ≥6.0) and improvement (CDI; decrease ≥1.0 from baseline EDSS score ≥2.0) over 6 years were analysed in TOP UK (n=134) and global (N=6149) cohorts using data from July 2007 to November 2017. Results: ARR decreased in UK patients from 2.21 in the year before initiation to 0.21 on natalizumab, paralleling the global decrease from 1.99 to 0.21. At 6 years, probabilities of CDW and CDI were, respectively, 27.8% and 34.4% in UK patients and 24.2% and 32.0% globally. Conclusions: Consistent with global TOP results, natalizumab ARRs and disability worsening rates remained low and disability improvement rates exceeded 30% at 6 years in the UK cohort. These results support natalizumab's long-term effectiveness in real-world settings. Support: Biogen. Disclosures will be included on the poster.